Continuous Consumer Market Measurement - Edward Arnold; Kent A. R (1989)
A general introduction to market measurement and the processes involved. Preface, Introduction, Retail Panels, Consumer Market Measurement Panels, Regular Interval Surveys, Conclusion, Bibliography, Index.